The Geopolitics of Real Estate : Reconfiguring Property, Capital and Rights. - Rogers, Dallas (Geopolitical bodies, material worlds., 2016)
A historical analysis of the geopolitics of real estate with settler-colonialism on the one side and the rise of über-wealthy foreign real estate investors on the other.